TRADITIONAL COMPLEMENTARY AND ALTERNATIVE MEDICINE AND ANTIRETROVIRAL TREATMENT ADHERENCE AMONG HIV PATIENTS IN KWAZULU-NATAL, SOUTH AFRICA - Peltzer, Karl; Friend-du Preez, Natalie; Ramlagan, Shandir; Fomundam, Henry; Anderson, Jane (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Adherence to antiretroviral medication in the treatment of HIV is critical, both to maximize efficacy and to minimize the emergence of drug resistance. The aim of this prospective study in three public hospitals in KwaZulu-Natal, South Africa, is to assess the use of Traditional Complementary and Alternative Medicine (TCAM) by HIV patients and its effect on antiretroviral (ARV) adherence 6 months after initiating ARVs. 735 (29.8% male and 70.2% female) patients who consecutively attended three HIV clinics completed assessments prior to ARV initiation and 519 after six months on antiretroviral therapy (ART) Results indicate that the use of herbal therapies for HIV declined significantly from 36.6% prior to antiretroviral treatment (ART) initiation to 7.9% after being on ARVs for 6 months. Faith healing methods, including spiritual practices and prayer for HIV declined from 35.8% to 22.1% and physical/body-mind therapy (exercise and massage) declined from 5.0% to 1.9%. In contrast, the use of micronutrients (vitamins, etc.) significantly increased from 42.6% to 87.4%. In multivariate regression analyses, ARV non-adherence (dose, schedule and food) was associated with the use of herbal treatment, not taking micronutrients and the use of over-the-counter drugs. The use of TCAM declined after initiating ARVs. As herbal treatment for HIV was associated with reduced ARV adherence, patients’ use of TCAM should be considered in ARV adherence management.